Freeze-thaw stability study of skinless pork longanisa with carrageenan - Dela Cruz, Cheryl Anne A.; Francisco, Ma. Leonora dL. (1999.)
The freeze-thaw stability of skinless pork longanisa with 0.5% ι-carrageenan, 0.5% κ-carrageenan and 0% carrageenan were evaluated in terms of physico-chemical characteristics and sensory attributes. These parameters were pH, % thaw drip, water-holding capacity, appearance, aroma, texture, juiciness, spiciness, overall flavor, and general acceptability. The analysis of variance and Duncan's Multiple Range test were used to determine difference between treatments. All three treatments were stable after being subjected to three frozen-thaw cycles. However, improved visual appearance, increased juiciness and increased rigidity were observed for treatments with carageenan. These also showed higher water-holding capacity and lower % thaw drip compared to the control treatments. From the two types of carrageenan, the skinless pork longanisa with κ-carrageenan exhibited the highest stability in all samples.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Pork -- Preservation; Sausages